(untitled) - Hoffmann, Frank W. (Lanham, Md., 2005)
The Authors compile a guide for students and librarians on collection practices, incorporating issues and methods spawned by the internet and electronic publishing. The focus is on university, public, and special libraries. The first part focuses on creating a "blueprint" for a library's holdings. The second part looks at developments in electronic collections
Keywords: Collection development (Libraries),Collection development (Libraries),Phát triển bộ sưu tập (thư viện),Phát triển bộ sưu tập (thư viện); United States,United States,Hoa Kỳ,Hoa Kỳ